THEORETICAL FOUNDATIONS AND MODERN STRUCTURE OF LINGUISTICS - Khudoynazarova Uglonoy Allamurodovna (Modern American Journals, 2025)
This article examines the formation, subject matter, and core tasks of linguistics as an independent scientific discipline. It provides a comprehensive analysis of the social nature of language, its structural organization, functional characteristics, and historical development within the framework of general linguistics. Particular attention is paid to the main branches of modern linguistics—extralinguistics, intralinguistics, and comparative linguistics—and their role in contemporary linguistic research.
Keywords: Linguistics, general linguistics, language system, language and society, extralinguistics, intralinguistics, comparative linguistics.